The association between witnessed and experienced harm and alcohol consumption amongst students at a large Western Australian university - Hart, Ellen; Burns, Sharyn (Wiley-Blackwell Publishing Ltd., 2015)
Introduction and Aims: Young Australian university students have been found to consume alcohol at a much higher level than their peers from the general population and are, therefore, also at a higher risk of witnessing and experiencing alcohol-related harm. This research measured the prevalence of alcohol consumption among 18–24 year old university students and the association between alcohol consumption and witnessed and experienced harms. Design and Methods: A random cross-sectional sample of university students aged 18–24 years (n = 2466) was recruited via the University Survey's Office and through random intercept at campus market day. All participants completed an online survey that included the Alcohol Use Disorders Identification Test, Alcohol Problems Scale and an additionally developed scale measuring witnessed harm. Results: Principal components analysis revealed three factors within the Alcohol Problems Scale; criminal and aggressive behaviour, health and emotional harms, and sexual harms. Students who consume alcohol at high risk levels were significantly more likely to score highly on each factor and were 1.5 times more likely to witness and experience harm than students who consume alcohol at low risk levels. Discussion and Conclusions: The categorisation of harm into factors is a novel approach to exploring harm and will inform more tailored and effective interventions. The positive association between alcohol consumption and alcohol-related harm provides support for previous findings. Implications for Practice: Based on the findings it is recommended that interventions addressing alcohol consumption in university students encompass a wide variety of strategies in order to comprehensively address the issue.